The effect of redox bacteria on the programmed cell death-1 cancer immunotherapy - Majid Nejati; Masoud Soheili; Mahmoud Salami; Mostafa Khedri (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Extracellular electron transferring (EET) or redox bacteria employ a shuttle of flavins to transfer electrons to the oxygen in the intestinal mucosa. Although clinical studies suggest that the gut microbiome modulates the efficiency of immune checkpoint therapy in patients with cancer, the modulation mechanisms have not been well-characterized yet. Experimental approach: In the present study, the oral gavage administration of Shewanella oneidensis MR-1 as a prototypic EET bacteria was assayed in a mouse model of lung cancer to determine the effect of EET bacterium on the efficacy of the programmed cell death protein 1 (PD1)-immune checkpoint therapy. Findings/Results: It was indicated that in vitro EET from S. oneidensis was mediated by riboflavins that were supplied through extrinsic sources. Co-administration of S. oneidensis and anti-PD 1 antibodies represent better tumor remission compared to the single-administration of each one; however, no statistically significant change was observed in the tumor volume. Conclusion and implications: More detailed studies are needed to definitively confirm the therapeutic effects of electrogenic bacteria in patients with cancer. Given the findings of the present study, increasing flavin compounds or EET bacteria in the intestine may provide novel strategies for modulating cancer immunotherapy.